Generating 3D Depiction for a Future ECDIS Based on Digital Earth. (November 2014) - Liu, Tao; Zhao, Depeng; Pan, Mingyang
<x content-type="archive" xml:space="preserve">Abstract</x> An Electronic Navigational Chart (ENC) is a two-dimensional abstraction and generalisation of the real world and it limits users' ability to obtain more real and rich spatial information of the navigation environment. However, a three-dimensional (3D) chart could dramatically reduce the number of human errors and improve the accuracy and efficiency of manoeuvring. Thus it is important to be able to visualize charts in 3D. This article proposes a new model for future Electronic Chart Display and Information Systems (ECDIS) and describes our approach for the construction of web-based multi-resolution future ECDIS implemented in our system Automotive Intelligent Chart (AIC) 3D ECDIS, including multi-resolution riverbed construction technology, multi-layer technology for data fusion, Mercator transformation of the model, rendering and web publishing methods. AIC 3D ECDIS can support global spatial data and 3D visualization, which merges the 2D vector electronic navigational chart with the three-dimensional navigation environment in a unified framework and interface, and is also published on the web to provide application and data service through the network.